If and are positive integers such that, then find the value of
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The above equation can be rearranged and written as a − b a + b − a b = 0 ⇒ a ( 1 − b 1 ) + b ( 1 − a 1 ) = 0 .
Now there are three cases,
Case 1 : first term > 0 and second term < 0 ,
Case 2 : first term > 0 and second term < 0 ,
Case 3 : first term = 0 and second term = 0
If we consider case 1 then we get that 1 − a 1 < 0 , which implies that a < 1 which is not possible since a is a positive integer. Similarly case 2 also does not hold. So the only possibility is case 3 where both the terms are equal to zero. Thus equating 1 − ( b 1 ) = 0 and 1 − ( a 1 ) = 0 , we get a = 1 and b = 1 . Therefore the value of a 2 + b 2 = 1 + 1 = 2 .